2021
DOI: 10.1016/j.jseint.2021.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Less than 9.5-mm coracohumeral distance on axial magnetic resonance imaging scans predicts for subscapularis tear

Abstract: Background Diagnosis of subscapularis (SSC) tendon lesions on magnetic resonance imaging (MRI) can be challenging. A small coracohumeral distance (CHD) has been associated with SSC tears. This study was designed to define a specific threshold value for CHD to predict SSC tears on axial MRI scans. Methods This retrospective study included 172 shoulders of 168 patients who underwent arthroscopic surgery for rotator cuff tear or glenohumeral instability. Diagnostic arthros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Compared to the unaffected side, the thickening of the CHL on the affected side was similar in both groups (difference: SIS = 0.6 mm and SSCL = 0.7 mm). Previous studies also reported thicker CHLs in other shoulder pathologies, such as frozen shoulder and anterior instability [ 26 , 27 ]. Thus, the CHL thickness in SIS patients could be related to the occurrence of subcoracoid impingement.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Compared to the unaffected side, the thickening of the CHL on the affected side was similar in both groups (difference: SIS = 0.6 mm and SSCL = 0.7 mm). Previous studies also reported thicker CHLs in other shoulder pathologies, such as frozen shoulder and anterior instability [ 26 , 27 ]. Thus, the CHL thickness in SIS patients could be related to the occurrence of subcoracoid impingement.…”
Section: Discussionmentioning
confidence: 71%
“…Similar to this finding, our results showed that the CHD was narrowest in IRFA and widest in ER positions. Reichel et al [ 26 ] suggest that a CHD width of less than 9.5 mm can predict SSC lesion. Regarding our results, the narrow CHD in CHDIR (9.4 mm) and CHDIRFA (8.7 mm) on the affected side might cause possible impingement and subsequently SSC lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the unaffected side, the thickening of the CHL on the affected side was similar in both groups (difference: SIS = 0.6 mm and SSCL = 0.7 mm). Previous studies also reported thicker CHLs in other shoulder pathologies, such as frozen shoulder and anterior instability [25,26]. Thus, the CHL thickness in SIS patients could be related to the occurrence of subcoracoid impingement.…”
Section: Discussionmentioning
confidence: 79%
“…Similar to this nding, our results showed that the CHD was narrowest in IRFA and widest in ER positions. Reichel et al [25] suggest that a CHD width of less than 9.5 mm can predict SSC lesion. Regarding our results, the narrow CHD in CHDIR (9.4 mm) and CHDIRFA (8.7 mm) on the affected side might cause possible impingement and subsequently SSC lesion.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Most recently, Hodax et al reported a CHD distance of 13.7 mm as the lower limit of normal, which was measured in 714 healthy asymptomatic patients. [26] Both postoperative and preoperative measurements were below the normal range reported by Reichel et al [25] Unlike the clinical studies mentioned above, this study is the first to report a negative relationship between gain in belly press strength and postoperative CHD. This may partially explain the absence of the beneficial effect of concomitant coracoplasty reported in the literature in cases where subscapularis tendon repair is required.…”
Section: Discussionmentioning
confidence: 99%